(-)-Epigallocatechin-3-gallate encapsulated realgar nanoparticles exhibit enhanced anticancer therapeutic efficacy against acute promyelocytic leukemia. (1st January 2019) - Fang, Wei; Peng, Zhao Liang; Dai, Ya Ji; Wang, Dian Lei; Huang, Peng; Huang, He Ping
Abstract: Realgar and (-)-Epigallocatechin-3-gallate (EGCG) are natural medicines that inhibit cancer cell growth, resulting in inhibition of formation and development of tumors. The anticancer effects of realgar and EGCG were greatly improved following formulation as nanoparticles. EGCG has received increased attention as a drug carrier. The aim of this study was to prepare a new nanomedicine, (EGCG-RNPs), in which encapsulated nano-realgar. EGCG-RNPs were prepared by coprecipitation and characterized by transmission electron microscopy (TEM), differential scanning calorimetry (DSC), particle size and zeta potential, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and in vitro release. Furthermore, we evaluated the antiproliferative effects of EGCG-RNPs on HL-60 cells in vitro, antitumor effect by intratumoral injection of EGCG-RNPs into solid tumors derived from APL HL-60 cells in vivo. Possible mechanisms were evaluated using uptake and efflux experiments in HL-60 cells. The results showed that the average particle size and zeta potentials of EGCG-RNPs was 200.3 ± 1.23 nm and −46.8 ± 1.31 mV. Controlled release of EGCG-RNPs was sustained and continued up to 72 h in vitro. Compared with nano-realgar and EGCG + RNPs (EGCG and nano-realgar physical mixing), EGCG-RNPs significantly inhibited growth of HL-60 cells. In a solid tumor model, EGCG-RNPs decreased tumor volumes, with an inhibitory rate of 60.18% at a dose of 70 mg · kg −1 . The mechanisms of antitumor improvement may correlate with the increased uptake of realgar and prolonged the retention time of realgar in HL-60 cells due to EGCG as a carrier. EGCG-RNPs could enhance anticancer therapeutic efficacy for acute promyelocytic leukemia.